AKUNTABILITAS WARGA BELAJAR PAKET A B C DALAM PROSES PEMBELAJARAN DI PKBM PELITA RIAU - Ritonga, Siti Zulaiha; Achmad, Said Suhil; Sumardi, Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the Accountability of Citizens Learning Package A B C while studying at PKBM Pelita Riau. The formulation of the problem in this study is how high is the accountability of citizens learning the A B C package in the learning process in Pelita Riau PKBM?. And the purpose of this study was to determine the level of accountability of citizens learning the A B C package in the learning process in Pelita Riau PKBM. This study has 3 indicators, namely (1) responsibility (2) obligation, and (3) ability to give answers. The population in this study were 64 study residents. The sample used is proportional stratified random sampling technique that is sampling that is used when members of the population are not homogeneous con sisting of homogeneous or proportional strata groups (Sugiyono, 2012: 93). The data collection technique in this study was a questionnaire technique, which amounted to 40 statements. Data were obtained from 38 respondents for the study sample and 20 people for the trial. After the questionnaire was tested, there were 2 invalid items, and the researcher did not discard invalid statements, because when disposing of invalid items one by one, the researcher found an invalid item again. So the researcher decided not to discard invalid items. Based on the results of the study, on average, 3 indicators of the mean value for the accountability variable of the citizens learning the A B C package in the learning process in Pelita Riau PKBM are high, with Mean 3.89 with SD 0.78. The interpretations obtained for each accountability indicator of citizens learning the A B C package in the learning process in Pelita Riau PKBM are all high.Key Words: Accountability, Accountability of Citizens Learning Package A B C